2006
DOI: 10.1002/agr.20088
|View full text |Cite
|
Sign up to set email alerts
|

Market segment analysis to target young adult wine drinkers

Abstract: Consumer segmentation in the wine industry takes on many forms: demographic, geographic, behavioral, and others. In the United States, one of the most promising new demographic segments is the Millennial or Echo Boomer segment, which is being targeted by many consumer industries due to its size and buying power. For the wine industry, this group currently fits the legal drinking age range of 21 to 28. This empirical study describes the perceptions and attitudes of 108 Millennials regarding wine and what the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
190
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(208 citation statements)
references
References 5 publications
15
190
2
1
Order By: Relevance
“…Targeting Generation Y consumers, the specific involvement level is crucial in the consumer's response to wine. Moreover, as in the literature often described (Barber et al, 2008b;Thach and Olsen, 2006), our study supported that Generation Y is striving for fun and pleasure, reflecting in the significant influence of the individual value on the wine consumption behaviour. Focusing on the Generation Y, marketers should therefore likewise the communication with Generation X include personal enjoyment and hedonic experiences in marketing strategies.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…Targeting Generation Y consumers, the specific involvement level is crucial in the consumer's response to wine. Moreover, as in the literature often described (Barber et al, 2008b;Thach and Olsen, 2006), our study supported that Generation Y is striving for fun and pleasure, reflecting in the significant influence of the individual value on the wine consumption behaviour. Focusing on the Generation Y, marketers should therefore likewise the communication with Generation X include personal enjoyment and hedonic experiences in marketing strategies.…”
supporting
confidence: 69%
“…Various studies have shown that considerable differences in wine consumption can be identified across generations what supports the market segmentation on the basis of age cohorts (e.g. Chrysochou et al, 2012;Agnoli et al, 2011;Barrena and Sanchez, 2009;Thach and Olsen, 2006;Thomas and Pickering, 2005). With respect to the benefits of wine consumption, it was found that young consumers perceive wine as a beverage, playing an important role in social occasions (Olsen et al, 2007).…”
Section: Cross-generational Wine Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bernabéu et al (2012) observa que la producción orgánica es un atributo relativamente importante para los consumidores jóvenes. Adicionalmente, los jóvenes han demostrado dar una mayor importancia al precio del vino y al diseño (Thach & Olsen, 2006). En España, García, Barrena, y Grande (2013) observan que los jóvenes están más preocupados por un estilo saludable, y que solo un pequeño grupo de ellos tiene una vaga idea de las denominaciones de origen.…”
Section: Importancia De Los Atributos a Nivel De Las Generaciones Etaunclassified